Uso, consumo e reuso de água e aproveitamento da água da chuva em indústrias automotivas - Vargas, Liz Danielle Monteiro (2024)
Faced with demands from the international market and other interested parties (suppliers, customers, community, government, among others) for the adoption of more sustainable industrial practices, the automotive industry faces the challenge of minimizing the pressure that its activities place on water resources. In this sense, this study aimed to present a global panorama characterizing the relationship between water resources and the automotive sector, with special emphasis on the use, consumption, reuse of water and use of rainwater in industries in the sector. To this end, global sustainability reports from 15 manufacturing companies in the automotive sector were evaluated. These documents containing information regarding the use and consumption of water, as well as projects for water reuse and the use of rainwater were available on their websites. Information was extracted from the reports on use, water consumption, water reuse, use of rainwater, water use per unit produced, and effluent generation. Furthermore, data from the Aqueduct Water Risk Atlas database was used to analyze the location of the companies studied about global regions with water stress. Among the companies studied, Toyota, Volkswagen and Honda, respectively, stand out as those that use the most water, respectively. Most companies use groundwater, with Iveco and CNH being the automakers with the highest percentage of use of this source. Greater water consumption was observed for the companies Honda and Hyundai, while the highest generation of effluents was attributed to Toyota and Volkswagen. The results generally indicated a tendency to reduce use and consumption for most companies evaluated over the last five years. It was identified that 80% of industries reuse water. However, only five companies use rainwater. As for water efficiency and the intensity with which this resource is used, these two indexes show a downward trend in the companies analyzed. All 15 automotive companies have at least four plants installed in areas with high or extremely high levels of water stress. The study also showed that many companies do not provide clear information on their reports and there is also no evident concern about areas experiencing water scarcity and impairment groundwater levels. The results of this research can help automotive companies identify opportunities to improve water management, contributing to a reduction in use and consumption through reuse and rainwater harvesting projects. It also allows companies to be alerted to the risk of shortages in at-risk areas.